5ARI and PSA: open questions. Issue 24 (July 2014) - Tubaro, Andrea; Puccini, Federica; De Nunzio, Cosimo
No consensus has ever been reached on the predictive value of serum prostate specific antigen (PSA) for the diagnosis of prostate cancer. Limitations of PSA testing in clinical practice have been often discussed in the peer-reviewed literature following data derived from clinical trials such as the Prostate Cancer Prevention Trial (PCPT) and the Reduction by Dutasteride of Prostate Cancer Events (REDUCE) study that showed a linear rise in the risk of prostate cancer with increasing PSA levels. Benign prostatic hyperplasia is a known confounding factor for the use of PSA as a marker of prostate cancer. Increased prostate volume observed with ageing, urinary retention, acute and chronic inflammatory conditions of the prostate, sexual activity and digital rectal examination may all cause an increase of PSA values. Both finasteride and dutasteride, 5-alpha reductase inhibitors (5ARI) used in the treatment of BPH, are known to induce a significant decrease of serum PSA levels close to 50%. The observed change in PSA values following 5ARI treatment has raised questions about the accuracy of PSA testing for the early diagnosis of prostate cancer in patients on finasteride/dutasteride treatment. Careful analysis of data from various clinical trials on pharmacological treatment of LUTS due to BPH suggested that the accuracy of PSA testing is not just maintained but rather increased following 5ARI use. Then, the question of PSA accuracy during 5ARI treatment can be considered closed.